A Refined Saccharomyces Cerevisiae-Induced Pyrexia Model In Rats For Specific Antipyretic Preclinical Screening - Putra, Oktavian Arya; Wardhani, Bantari Wisynu Kusuma; Riska, Riska; Ramadhan, Nuzula Rijal Nur; Pamungkas, Fajrin Yudha; Al Baariq, Hisyam Nabil Najmuddin; Wahyuningtias , Dita Sheila Putri; Khairunnisa, Rahma; Ulhaq, Oktania Dhiya; Azis, Nurul Magfirah; Guselsa, Fricelia Aura; Siregar, Tika Hafzara; Khairullah, Aswin Rafif (Biomedical Journal of Indonesia, 2025)
Introduction. A fever-specific, reliable animal model is necessary to screen the antipyretic activity of pharmacological agents, especially to differentiate their action from broad anti-inflammatory activity. The present investigation was directed towards standardizing the yeast-induced pyrexia model in Sprague Dawley rats for screening the antipyretic activity of paracetamol. Methods. Male Sprague Dawley rats were placed into three groups (5 each): normal control, pyrexia-induced untreated, and paracetamol-treated. Pyrexia was induced by subcutaneous injection of 40% aqueous suspension of Saccharomyces cerevisiae (10 mL/kg b.w.). Paracetamol-treated rats were given a single oral dose of 150 mg/kg following pyrexia induction. Rectal temperature was measured at intervals of 30 minutes for 180 minutes. Results. Saccharomyces cerevisiae injection elicited a satisfactory febrile response in both pyrexia-induced groups. In the paracetamol-treated group, there was a considerable decrease in rectal temperature from 90 minutes, and the difference was statistically significant (p < 0.05) when compared with the untreated group. The model was able to distinguish the antipyretic effect of paracetamol from natural thermoregulatory fall in controls. Conclusion. This S. cerevisiae pyrexia model in mice is a specific and reproducible platform for antipyretic drug evaluation. The ability to dissociate antipyretic mechanisms from accompanying inflammatory processes is what makes it an acceptable model for future pharmacological screens. The addition of fever-specific biomarkers, i.e., hypothalamic metabolites and PGE₂, is suggested to also offer mechanistic insight and translational value.